A Survey On Medical Digital Imaging Of Endoscopic Gastritis. - Mohd Yacob, Yasmin; Mat Sakim, Harsa Amylia; Baharudin, Norain; Lee, Yeong Yeh; Mat Isa, Nor Ashidi (2009)
This paper focuses on researches related to medical digital imaging of endoscopic gastritis.